The princess and the goblin - MacDonald, George, 1824-1905.; Smith, Jessie Willcox, 1863-1935 (New York : Books of Wonder : W. Morrow, 1986)
A little princess is protected by her friend Curdie from the goblin miners who live beneath the castle.
Sequel: The princess and Curdie.
Keywords: Goblins -- Juvenile fiction; Princesses -- Juvenile fiction; Fairy tales -- Juvenile fiction